Studying international migration in the long(er) and short(er) durée: contesting some and reconciling other disagreements between the structuration and morphogenesis approaches - Morawska, E (International Migration Institute, 2011)
This paper contests some and reconciles other disagreements between the structuration and morphogenesis theories – two approaches in present-day sociology which aim at bridging the macro–micro gap in social theorizing, but whose advocates have been either indifferent to or openly at odds with each other, instead of engaging in a close intellectual collaboration. The empirical illustrations of my arguments come from local statistical surveys and ethnographic studies conducted in Polish villages from the onset to the decline of mass transatlantic migration in the period 1870s–1930s.